Productivity Growth and Structural Reform in Bulgaria : Restarting the Convergence Engine - Pouvelle, Cyril (IMF Working Papers; Working Paper, 2012)
Labor productivity levels in Bulgaria lag well behind that in the EU, weighing on the convergence process. Stronger productivity growth would allow Bulgaria to close the income gap with the EU average more quickly and to alleviate the structural problems in its labor market, reflected in its high long-term and youth unemployment. Our analysis of the drivers of labor productivity suggest that for Bulgaria closing the gap with EU standards in the areas of institutional and infrastructure quality, goods market efficiency, higher education, and innovation would permanently boost productivity growth by a total of 1 percentage point a year. This would be enough to close the income gap with the EU average by 2040, compared to the status quo where it would take an additional 10 years.